“Spill link dong kak!”: A Byte-Sized Shopping Experience in Youth Consumption Culture in Surakarta - Endang Purwasari; Roudlotul Jannati R.N. Yudhitya; Maharani Nur Azizah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2025)
The development of digital applications that can be accessed by the younger generation, both for entertainment and shopping, is rapid. The presence of the TikTok platform, which has succeeded in winning the hearts of the younger generation, makes this application a favorite. TikTok had become a mainstay for shopping some time ago before it was closed due to regulation changes. This research offers the reasons behind the TikTok addiction among society, especially Generation Z in Surakarta. This research uses an ethnographic approach involving eight primary informants with the involvement of several people in accidental interviews. Data was collected using the in-depth interview method to understand the reasons for using TikTok and shopping preferences through this platform. Meanwhile, participant observation was carried out by observing shopping accounts and influencers, followed by informants. Apart from that, researchers also made purchases of products presented by informants. Apparently, TikTok not only offers entertainment but is also a space for its users to form their own taste. Through short videos presented by the influencers they follow, users use them as references that can be imitated. Through this account, users also make decisions about purchasing products. Hence, TikTok users do not have the freedom to decide but there is an invisible hand in shaping market preferences and tastes. This paper discusses how neoliberalism, with its emphasis on individual freedom and economic rationality, has given birth to a new configuration in the consumption patterns of society, especially Generation Y and Z. In this context, digital platforms such as TikTok not only act as a means of entertainment and information but also become a strategic arena for the practice of contemporary capitalism. Through its personalized, spontaneous, and algorithmic visual approach, TikTok has managed to shape the tastes, preferences, and consumption behavior of its users.